2003
DOI: 10.1046/j.1365-2842.2003.01069.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of the hyoid bone and posterior surface of the tongue in prognathism and micrognathia

Abstract: In order to study relationship of the hyoid bone and posterior surface of the tongue in prognathism and micrognathia, we focused on the effect of the tongue on the upper airway lumen in 16 patients with Angle's Class II and 51 patients with Angle's Class III, and assessed the position of the hyoid, the depth from the posterior surface of the tongue, from the bottom of the vallecula and from hyoid bone to the posterior pharyngeal wall using lateral cephalograms. We were able to assess significant correlations b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 27 publications
6
19
0
2
Order By: Relevance
“…Current measurements showed that hyoid bone tended to move anteriorly, which was more noticeable in the treatment group and were probably due to the more anterior displacement of the mandible, in line with the findings of Jena et al [20]. As the genioglossus muscle is the main protruder of the tongue, it acts as an accessory respiratory muscle, resulting in advancement of the base of the tongue and dilation of the airway [29,30]. Zhou et al [27] also found that hyoid moved forward and downward following treatment with FR-I.…”
Section: Discussionsupporting
confidence: 85%
“…Current measurements showed that hyoid bone tended to move anteriorly, which was more noticeable in the treatment group and were probably due to the more anterior displacement of the mandible, in line with the findings of Jena et al [20]. As the genioglossus muscle is the main protruder of the tongue, it acts as an accessory respiratory muscle, resulting in advancement of the base of the tongue and dilation of the airway [29,30]. Zhou et al [27] also found that hyoid moved forward and downward following treatment with FR-I.…”
Section: Discussionsupporting
confidence: 85%
“…The hyoid position represents tongue posture and function, and hyoid structures are guided to an anterio-inferior position to avoid compromising the vital airway passage as a compensatory action. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Yamaoka et al [28] found that the tongue root was situated more posteriorly in Class II females subjects compared with Class III ones. Also, the change in hyoid bone position and lower pharyngeal airway space caused by anteroposterior position of the mandible is well documented [29].…”
Section: Lowermentioning
confidence: 96%